Diagnostico técnico e hidráulico del sistema de abastecimiento de agua potable del municipio El Águila, Valle del Cauca (2020)
At present, the technical and hydraulic diagnosis of the drinking water supply system of the municipality of El Águila, Valle del Cauca is found, where the current hydraulic operation of the components, intakes, grit, tanks and means of transport is evaluated, comparing the results with the regulations valid for the year 2020